Identifying Factors Associated with the Recurrence of Tic Disorders - Yixin Zhang; Nong Xiao; Xilian Zhang; Zhenhua Zhang; Jiusi Zhang (Brain Sciences, 2022)
Tic disorders are neurological disorders that are prone to fluctuation and recurrence. It is important to study the factors related to disease recurrence and to subsequently provide suggestions for clinical treatment. A retrospective study was conducted to assess patients with recurrent and non-recurring tic disorders diagnosed in the Pediatric Tic Disorder Clinic of the First Affiliated Hospital of Tianjin University of Traditional Chinese Medicine, China, and to extract various factors—such as fetal status; medication, allergy, and family history; social and psychological factors; blood lead content; electroencephalogram (EEG); disease duration; type of tics; and disease severity—and identify factors associated with recurrence. The recurrence rate of tic disorders was approximately 45.10% in this study. The childbirth conditions, surgery/trauma, respiratory tract infection, allergy, stress, consumption of tiapride, and severity of tic disorders were factors related to and affected disease recurrence.